2019
DOI: 10.1029/2019jd031377
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Ocean Response and Its Feedback to Typhoon Hato (2017) Over the South China Sea: A Numerical Study

Abstract: The coastal ocean response and feedback to Typhoon Hato (2017) were studied based on high‐resolution numerical simulations using both a coupled and an uncoupled cloud‐resolving model. As a category 3 landfalling typhoon that moved west‐northwestward across the northern South China Sea, Hato (2017) rapidly intensified prior to its landfall and induced significant impacts on the coastal water column, causing warm and cold patches in sea surface temperature (SST) over the continental shelf to the right of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…Several studies have shown that the presence of stratification prior to storm arrival can significantly reduce the intensity of impending storms, via aheadof-eye SST cooling 7,8,10,11 . Conversely, other studies have suggested or shown that anomalously warm conditions on shelves have contributed to the intensification of hurricanes through landfall 6,[12][13][14] .…”
mentioning
confidence: 94%
“…Several studies have shown that the presence of stratification prior to storm arrival can significantly reduce the intensity of impending storms, via aheadof-eye SST cooling 7,8,10,11 . Conversely, other studies have suggested or shown that anomalously warm conditions on shelves have contributed to the intensification of hurricanes through landfall 6,[12][13][14] .…”
mentioning
confidence: 94%
“…Note the period after 0000 UTC 23 August, when stronger LHF occurs in CPL storm eyewall with the even weaker tangential wind than FO storm. The local SST becomes higher in the CPL experiment ( Figure 10c) because of the TC induced hot onshore surface water [49]. This could further suggest the important role of local SST in modulating the energy source, and thus the inner-core evolution in storms.…”
Section: Mechanisms Analysismentioning
confidence: 86%
“…To reproduce the ocean responses to the typhoon forcing, ROMS was coupled to WRF through the Model Coupling Toolkit (MCT). ROMS is a free-surface primitive equation ocean model in sigma vertical coordinate, which has been widely used in estuaries, coastal [48,49], and open ocean simulations [17,50] for both research and operational forecasting (model is developed and supported mainly by researchers at the Rutgers University, University of California Los Angeles, codes available at http://www.myroms.org). Configured with 30 vertical levels and one horizontal domain, the single domain of ROMS covered the same region as WRF did with the horizontal resolution of 18 km, which means that the variables could be transferred from grid to grid between two models.…”
Section: Model and Configurationsmentioning
confidence: 99%
“…These results present a new framework for understanding how a stratified ocean may respond to TC forcing along steep coastal margins. Previous work has found three predominant coastal ocean baroclinic responses to TC winds during the initial forced stage: (i) cooling from shear-induced mixing ( 14 , 15 ), (ii) restricted cooling due to downwelling and offshore advection of cold bottom water ( 16 ), and (iii) warming due to downwelling circulation and suppression of upwelling ( 20 , 21 ). Our observations document a previously unidentified response, whereby offshore-directed TC winds along a relatively narrow insular shelf with a steep slope result in sustained, warm SSTs throughout the storm, despite the influx of increasingly cold waters at depth.…”
Section: Discussionmentioning
confidence: 99%